O papel da Olimpíada de Língua Portuguesa: escrevendo o futuro no processo de formação continuada dos professores participantes - Altenfelder, Anna Helena (2010)
The Olympiad of Portuguese Language Escrevendo o Futuro, is an initiative of the Ministry of Education and promotes a text contest for elementary school students. The program includes a guidance material for the teachers that helps the students to develop and improve the texts that will compete. This study aims to understand and analyze how the theoretical approaches and the activities proposed in this material, Teachers Orientation Books affect the practice and the comprehention of teaching text production. Therefore, the focus of this study is the activity and development of the teacher s consciousness. For a better undertanding of this phenomenon, the discussion was based upon the socio-historical psychology of L. S. Vygotsky and his followers. In this perspective, it is presented the genesis and development of the human psyche, emphasizing the activity categories, consciousness and mediation. Social function of schools, the relationship between education and development and the different aspects that characterize and constitute the teaching activity is also discussed. The research involved 356 teachers from all over Brazil, contestants of the 3rd Olympiad of Portuguese Language, held in 2006, who have answered questionnaire that was sent to all registered schools. An effort to capture the range of meanings expressed by the contestants was made for data analysis. Taking the answers to the different questions in the questionnaire as a starting point, it was made an effort to organize them into clusters that could reveal the movements made by the teachers to face the task of teaching their students text production, supported by the didactic sequence proposed in the submitted material. Thus, it was possible to apprehend the experienced emotions by teachers in facing the task of guiding their students to produce texts, which have generated new needs that have given the reasons that led them to overcome difficulties and obstacles that allowed them, on one hand, to break with the concepts, beliefs attitudes and ways of acting and, on the other hand, discover new ways of thinking, acting and feeling, not only the teaching of text production but the teaching activity in a broader sense, in other words, it was possible for the teachers build new meanings for his role as mediator